Collections of Customary Law in East Central Europe Using the Example of Opus Tripartitum - Vladár, Vojtech (Lectures on East Central European Legal History, 2022)
Customary law dominated at the beginning of the development of all legal systems, and this status persisted until the times when they were equaled by laws of the authorities disposing of necessary state power. However, even then, customs were not instantly sidelined, and these two sources were engaged in competition for centuries. Mention was topical, with certain exceptions and individualities, even regarding the legal systems of Central and Eastern Europe. The most widely known compilation of this provenance was Stephen Werbőczy’s collection of customary law from the second decade of the 16th century that became famous under the name Opus Tripartitum. Using it as an example, we can demonstrate typical legal development in this period, not only for the Kingdom of Hungary but also for several neighboring countries. The main goal of this article is to point out the historical development of its origin, identify the authorial spirit in which it was written, and clarify the conflict between customary and written law, which was resolved determinatively by reason of this compilation in favor of the first for the next centuries.KEYWORDS: codification efforts, Stephen Werbőczy, Opus Tripartitum, structure of the compilation, legal custom, law, reasons for non-promulgation, obligatory force, dominance and weakening of the achieved positions, other countries of Central and Eastern Europe.